2021
DOI: 10.1177/08987564211061621
|View full text |Cite
|
Sign up to set email alerts
|

Success of Feather Margin Preparation for Full Metal Prosthodontic Crowns in the Canine Teeth in 84 Pet and Working Dogs (2005-2017)

Abstract: Medical and dental records of Veterinary Dental Specialties and Oral Surgery were searched to identify dogs that received full metal prosthodontic crowns on canine teeth, using a feather or knife edge preparation between 2005 and 2017. A total of 160 teeth in 84 dogs were included in the study. Current follow-up by telephone, electronic mail, or electronic messaging was conducted, in addition to thorough record review for in-person recheck examinations. Treatment was considered successful if the prosthodontic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Crowns are made at specialist laboratories from an impression of the tooth, and these are then cemented in place at a separate appointment. In a study of 160 crowns, the authors reported no loss of crown or further injury to the tooth in 97.5 per cent of cases, suggesting that prosthodontic crown therapy is a suitable option for protecting previously injured teeth in dogs (Ribka and Niemiec 2021).…”
Section: Endodontic Proceduresmentioning
confidence: 99%
“…Crowns are made at specialist laboratories from an impression of the tooth, and these are then cemented in place at a separate appointment. In a study of 160 crowns, the authors reported no loss of crown or further injury to the tooth in 97.5 per cent of cases, suggesting that prosthodontic crown therapy is a suitable option for protecting previously injured teeth in dogs (Ribka and Niemiec 2021).…”
Section: Endodontic Proceduresmentioning
confidence: 99%